IMPROVING THE METHODS OF PLANNING LINEAR STRUCTURES USING MODERN TECHNOLOGIES (Intent Research Scientific Journal, 2023)
A description of geodetic methods corresponding to the current level of development of the coordinate base is presented. The importance of improving methods for assessing, predicting and controlling the deformed state of the earth's surface and rock mass is emphasized. The issue of satellite positioning technology for creating reference surveying networks is considered, in terms of assessing the accuracy of determining the coordinates of points when using one or several base stations. The original technology of observation of Earth's surface deformations in undermined territories is shown, which makes it possible to obtain the spatial position of the displacement trough.